1996
DOI: 10.1097/00007632-199601010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the Spinal Dura

Abstract: Spinal dura does not have a rich innervation of calcitonin gene-related peptide- and substance P-positive nerve fibers or a robust population of mast cells. The spinal dura may serve as a protective covering. Unlike the cranial dura, it may not be implicated in the pathogenesis of pain. Additional studies on primate and human spinal dura are warranted to corroborate findings that the spinal dura may be relatively insensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Kumar et al [39] reported a sparse innervation of CGRP-and SP-positive neurons in the ventral part of the dura mater lumbalis, but observed no fibers in the dorsal dura. In contrast to this finding, other authors demonstrated a network of CGRPand SP-positive primary afferents in the ventral dura mater lumbalis and a less dense innervation in the dorsal aspects [1,2,30,39]. The present study confirms the sensory peptidergic innervation of the ventral as well as the dorsal parts of the lumbar dura and adds quantitative data on their innervation density.…”
Section: Innervation Of the Spinal Dura Mater Lumbalissupporting
confidence: 54%
“…Kumar et al [39] reported a sparse innervation of CGRP-and SP-positive neurons in the ventral part of the dura mater lumbalis, but observed no fibers in the dorsal dura. In contrast to this finding, other authors demonstrated a network of CGRPand SP-positive primary afferents in the ventral dura mater lumbalis and a less dense innervation in the dorsal aspects [1,2,30,39]. The present study confirms the sensory peptidergic innervation of the ventral as well as the dorsal parts of the lumbar dura and adds quantitative data on their innervation density.…”
Section: Innervation Of the Spinal Dura Mater Lumbalissupporting
confidence: 54%
“…Some recent studies (Groen et al, 1988;Kallakuri et al, 1998;Kumar et al, 1996;Yamada et al, 1998) have provided new light on this topic but, in any case, did not furnish an unequivocal interpretation of the different pattern of innervation. Our experimental observations are confined to human and rodents' dura mater and led us to describe some interesting findings in the examined species.…”
Section: Introductionmentioning
confidence: 96%
“…The ventral dural nerves may extend up to eight segments, with a great amount of overlap between adjacent nerves. Somatosensory (CGRP-and SP-positive) fibers along dural root sleeves in the cervical and lumbar regions have also been demonstrated (Kumar et al, 1996). The majority of these fibers are autonomic (Groen et al, 1988).…”
Section: Innervation Of the Meningesmentioning
confidence: 55%